Fear, victimization, and stress among urban public school teachers - Dworkin, Anthony Gary [Verfasser]; Haney, C. Allen [Verfasser]; Telschow, Ruth L. [Verfasser] (My University, 1988)
"Data from the National Institute of Education's Safe School Study Report suggested that teachers in American urban public schools are emotionally and physically victimized and that the result is heightened level of stress associated with teaching. This study, which is part of larger, longitudinal project, explores the linkages between reported experiences of victimization by 291 urban public school teachers and task-specific stressors in the performance of the teaching role. The level of reported stress and nature and degree of victimization differ by the grade level taught and the race of the teacher. Generally, minority teachers (black and brown) are less likely to report being stressed or victimized than are white teachers, while elementary school teachers report their work to be most stressful. There is no evidence of a specific causal ordering between fear of victimization and teachers stress. Rather, each may feed upon and faciliate the other." (author's abstract) ((en)) Auf der Grundlage einer Befragung von 291 amerikanischen Lehrern wird der Frage nachgegangen, inwieweit die Angst vor Gewalt und das Gefühl der Schikanierung durch Schüler zu einem erhöhten Arbeitsstress führt. Das Ausmass der Belastungen differiert nach Schulebene und Hautfarbe der Lehrer. (IAB)
Angst, Schikanierung und Stress bei Volksschullehrern
Keywords: P 3.2.3 Lehrer; G 2.3 Wandel von Arbeit & Wirtschaft; T 4.8 Arbeitswissenschaften; G 2.4.2 Lebenskonzepte, -stile, Werte; Lehrer; Stress; Berufsproblem; Arbeitsbelastung; Jugendkriminalität; Quantitative Angaben